Neurobehcet pediátrico. Presentación de un caso y revisión de la literatura. - Visaga, Maribel; Campos, Patricia; Bancalari, Ernesto; Romero, Félix; Hernandez, Herminio; Berrocal, Alfredo; Trelles, Luis; Calvo, Armando (Revista Médica Herediana, 2013)
The first peruvian pediatric case of Neuro-Behcet, who had seizures, hemiparesis and a magneic nuclear resonance with a pseudotumoral imagine is here presented